Plasticity and stress tolerance override local adaptation in the responses of Mediterranean holm oak seedlings to drought and cold - Gimeno, Teresa E; Pías, Beatriz; Lemos-Filho, José P; Valladares, Fernando (Tree physiology, 2009)
Plant populations of widely distributed species experience a broad range of environmental conditions that can be faced by phenotypic plasticity or ecotypic differentiation and local adaptation. The strategy chosen will determine a population's ability to respond to climate change. To explore this, we grew Quercus ilex (L.) seedlings from acorns collected at six selected populations from climatically contrasting localities and evaluated their response to drought and late season cold events. Maximum photosynthetic rate (A(max)), instantaneous water use efficiency (iWUE), and thermal tolerance to freeze and heat (estimated from chlorophyll fluorescence versus temperature curves) were measured in 5-month-old seedlings in control (no stress), drought (water-stressed), and cold (low suboptimal temperature) conditions. The observed responses were similar for the six populations: drought decreased A(max) and increased iWUE, and cold reduced A(max) and iWUE. All the seedlings maintained photosynthetic activity under adverse conditions (drought and cold), and rapidly increased their iWUE by closing stomata when exposed to drought. Heat and freeze tolerances were similarly high for seedlings from all the populations, and they were significantly increased by drought and cold, respectively; and were positively related to each other. Differences in seedling performance across populations were primarily induced by maternal effects mediated by seed size and to a lesser extent by idiosyncratic physiologic responses to drought and low temperatures. Tolerance to multiple stresses together with the capacity to physiologically acclimate to heat waves and cold snaps may allow Q. ilex to cope with the increasingly stressful conditions imposed by climate change. Lack of evidence of physiologic seedling adaptation to local climate may reflect opposing selection pressures to complex, multidimensional environmental conditions operating within the distribution range of this species.